CXCL1-Mediated Interaction of Cancer Cells with Tumor-Associated Macrophages and Cancer-Associated Fibroblasts Promotes Tumor Progression in Human Bladder Cancer - Miyake, Makito; Hori, Shunta; Morizawa, Yosuke; Tatsumi, Yoshihiro; Nakai, Yasushi; Anai, Satoshi; Torimoto, Kazumasa; Aoki, Katsuya; Tanaka, Nobumichi; Shimada, Keiji; Konishi, Noboru; Toritsuka, Michihiro; et al. (Neoplasia (New York, N.Y.), 2016)
Tumor-associated macrophages (TAMs) and cancer-associated fibroblasts (CAFs) are reported to be associated with poor prognosis, depending on their pro-tumoral roles. Current knowledge of TAMs and CAFs in the tumor microenvironment of urothelial cancer of the bladder (UCB) is limited. Therefore, we investigated the paracrine effect induced by TAMs and CAFs in the tumor microenvironment of human UCB. For this, we first carried out immunohistochemical analysis for CXCL1, CD204 (TAM marker), αSMA (CAF marker), E-cadherin, and MMP2 using 155 UBC tissue samples. Next, CXCL1-overexpressing clones of THP-1-derived TAMs and NIH3T3-derived CAFs were developed by lentiviral vector infection. The immunohistochemical study showed high CXCL1 levels in UCB cells to be associated with enhanced recruitment of TAMs/CAFs, higher metastatic potential, and poor prognosis. Three-dimensional (3D) co-culture of UCB cells and TAMs/CAFs suggested that CXCL1 production in TAMs/CAFs play an important role in cell-to-cell adhesion and interaction among cancer cells and these stromal cells. CXCL1-expressing TAMs/CAFs enhanced tumor growth of subcutaneous UCB tumors in nude mice when injected together. In addition, an experiment using the orthotopic bladder cancer model revealed that CXCL1 production in TAMs/CAFs supported tumor implantation into the murine bladder wall and UCB growth when injected together, which was confirmed by clinical data of patients with bladder cancer. Thus, CXCL1 signaling in the tumor microenvironment is highly responsible for repeated intravesical recurrence, disease progression, and drug resistance through enhanced invasion ability. In conclusion, disrupting CXCL1 signaling to dysregulate this chemokine is a promising therapeutic approach for human UCB.